Can a supranational medicines agency restore trust after vaccine suspensions? The case of Vaxzevria - Andrea Albanese; Francesco Fallucchi; Bertrand Verheyden (Global Labor Organization (GLO), 2021)
Over the first half of March 2021, the majority of European governments suspended Astrazeneca's Vaxzevria vaccine as a precaution following media reports of rare blood clots. We analyse the impact of the European Medicines Agency's (EMA) March 18th statement assuring the public of the safety of Vaxzevria and the immediate reinstatement of the vaccine by most countries on respondents' intention to get vaccinated. By relying on survey data collected in Luxembourg and neighbouring areas between early March and mid-April, we observe that the willingness to be vaccinated was severely declining in the days preceding the EMA statement. We implement a regression discontinuity design exploiting the time at which respondents completed the survey and find that the vaccine reinstatement substantially restored vaccination intentions.
Keywords: I12; I18; C21; H12; H40; 330; COVID-19; vaccine hesitancy; supranational regulation; public health; regression discontinuity design